Environmental Change and African Societies - Tischler, Julia; Haltermann, Ingo (Climate and Culture, 2019)
Environmental Change and African Societies contributes to current debates on climate change from the perspectives of the social sciences and the humanities. It charts past and present environmental change in different African settings as well as scenarios for the future.; Readership: Historians, social anthropologists, political scientists, geographers and anyone else interested in environmental change in Africa.